(untitled) (INNOVATIVE ECONOMY, 2019)
Busarieva T.H. COMPARATIVE CHARACTERISTICS OF CROSS-CULTURAL PECULIARITIES OF FORMATION OF TNC KNOWLEDGE MANAGEMENT SYSTEMS Purpose. The aim of the article is an analysis of the cross-cultural characteristics and differences of the American, European and Asian TNC knowledge management systems and their comparison with the respective corporate cultures. Methodology of research. The methodological basis of the article is the methods and forms of scientific knowledge adopted in national science, such as: systematic approaches, methods of comparison and synthesis, methods of abstract logical evaluation, methods of detail, empirical methods, expert assessments, etc. In particular, the main methods used in writing this article are: the observation method (when analyzing the activities of American, European, and Asian TNCs); methods of grouping and generalization (when distinguishing cross-cultural features of knowledge management TNC); methods of detail (in determining the specific characteristics of each of the proposed models). Findings. The cross-cultural characteristics and differences of the American, European and Asian TNC knowledge systems are highlighted and characterized. It is determined that the European approach to knowledge management developed in the Scandinavian peninsula, mainly in Sweden; at the same time, the Japanese approach was developed thanks to the works of such scientists as I. Nonaka and H. Takeuchi, who put forward the idea of a lack of knowledge for business development; The US approach aims at analyzing TNC activity and highlighting multilevel approaches to US development. It is proved that the creation of knowledge, regardless of the features of cross-cultural models of US companies, is the result of four processes that form a spiral of knowledge: socialization, combinations, externalization and internalization, and describe the transformation of knowledge between two forms: explicit and implicit. The peculiarities of the Ukrainian corporate culture are found to be: compassion for the losers, voluntary self-restraint of comfort, approval of collective efforts in work, attentive attitude to individualism, to achieving their own well-being at the expense of others; promotion and encouragement of employees based on their personal loyalty to the organization; transparency of decisions, secrecy, closeness of the organization to the outside world, and the existence of barriers between units. Originality. For the first time, models of cross-cultural peculiarities of the American, European and Asian TNC knowledge management systems and their impact on the formation of corporate culture have been identified and substantiated, which makes it possible to use the experience of leading TNCs in the world to improve the effectiveness of Ukrainian companies in the context of the development of the knowledge management system. Practical value. The results of the study can be used by Ukrainian companies with foreign capital to support the development of their knowledge management systems based on the successful implementation of the cross-cultural characteristics of American, European and Asian models. Key words: American system of knowledge management; European system of knowledge management; Asian system of knowledge management; cross-cultural differences; corporate culture.